An IS element-driven antisense RNA attenuates the expression of serotype 2 fimbriae and the cytotoxicity of Bordetella pertussis - Alexandre D’Halluin; Denisa Petráčková; Ivana Čurnová; Jakub Držmíšek; Jan Čapek; Peggy Bouquet; Loïc Henin; Rudy Antoine; Loïc Coutte; Camille Locht; Branislav Večerek; David Hot (Emerging Microbes and Infections)
Insertion sequences (IS) represent mobile genetic elements that have been shown to be associated with bacterial evolution and adaptation due to their effects on genome plasticity. In Bordetella pertussis, the causative agent of whooping cough, the numerous IS elements induce genomic rearrangements and contribute to the diversity of the global B. pertussis population. Previously, we have shown that the majority of IS-specific endogenous promoters induce the synthesis of alternative transcripts and thereby affect the transcriptional landscape of B. pertussis. Here, we describe the regulatory RNA Rfi2, which is transcribed from the Pout promoter of the IS481 gene BP1118 antisense to the adjacent fim2 gene encoding the major serotype 2 fimbrial subunit of B. pertussis. Among the classical bordetellae, Rfi2 is unique to B. pertussis, suggesting its specific role in virulence. We show that Rfi2 RNA attenuates fim2 transcription and, consequently, the production of the Fim2 protein. Interestingly, the mutant that does not produce Rfi2 displayed significantly increased cytotoxicity towards human macrophages compared to the parental strain. This observation suggests that the Rfi2-mediated reduction in cytotoxicity represents an evolutionary adaptation of B. pertussis that fine-tunes its interaction with the human host. Given the immunogenicity of Fim2, we further hypothesize that Rfi2-mediated modulation of Fim2 production contributes to immune evasion. To our knowledge, Rfi2 represents the first functionally characterized IS element-driven antisense RNA that modulates the expression of a virulence gene.